3D effects of a bone-anchored intra-oral protraction in treating class III growing patient: a pilot study - Mohammed Almuzian; Anas Almukhtar; Aman Ulhaq; Fahad Alharbi; M. Ali Darendeliler (SpringerOpen, 2019)
Abstract Objectives The aim of this prospective case series study is to assess the three-dimensional (3D) skeletal and soft tissue effects of the alternate rapid maxillary expansion and constriction (Alt-RAMEC) protocol in conjunction with a miniscrew-supported class III elastic wear in class III growing patients. Materials and methods Fourteen consecutive participants (mean age 12.05 ± 1.09 years), who displayed class III malocclusions with retrognathic maxillae, were recruited. A cone beam computed tomography (CBCT) scan was acquired before commencing treatment (T1). All participants were treated with a tooth-bone-borne rapid maxillary expansion (hybrid MARME) appliance that was activated by the Alt-RAMEC protocol for 9 weeks. This was followed by full-time class III elastics, delivering 400 g/side, to protract the maxilla. When a positive overjet was achieved, protraction was ceased and a post-treatment CBCT scan (T2) was taken. The 3D analysis of pre- and post-treatment CBCT scans was blinded. The scans were registered on the anterior cranial base. The Euclidean distance between the two extracted surface models of the pre- and post-treatment scans was displayed as a color surface map. Results All participants completed the intervention successfully. The majority of the participants showed protraction of the anterior maxillary region (71.4%) and in the zygomatic processes (64.2%). The maxilla significantly protracted (SNA 1.87° ± 1.06°; Vert.T-A 3.29 ± 1.54 mm), while the mandibular base significantly redirected posteriorly (SNB − 2.03° ± 0.85°, Vert.T-B − 3.43 ± 4.47 mm) and that was reflected on the ANB and Wits measurements. No adverse effects were observed. Conclusion Class III elastics combined with the Alt-RAMEC activation protocol of the hybrid MARME appliance is an effective treatment method for mild/moderate class III malocclusions. A long-term follow-up and comparisons with other treatment modalities are required.